LEGAL STATUS OF LAND RIGHTS CONTROLLED BY BUDDHIST RELIGIOUS FOUNDATIONS IN MEDAN CITY - Michelle Amanda Esitria Sumampow; Elvira Fitriyani Pakpahan; Kartina Pakpahan; Ramon Nafrial; Made Adhiguna Samvara (Magister Kenotariatan Universitas Pasundan, 2022)
The purpose of this study is to analyze the mechanism in the process of ownership of the property rights on the foundation land, as well as the factors that obstruct the process of ownership of the property rights on the foundation land, and to analyze the legal remedies available to a foundation so that land owned by the foundation but certified in the name of an individual can be changed to the foundation's name. The approach used was the juridical-empirical method, which is legal research carried out by combining a juridical legal approach with empirical elements. Literature review and interviews were employed as data collecting or processing techniques in this study. The research results obtained are based on Law 28 of 2004 concerning Amendments to Law 16 of 2001 on Foundations at ensuring greater legal certainty and order. Therefore, the Management of the Buddhist Religious Foundation in Medan City is required to continue the process of transferring for rights or applying for rights at the National Land Office in an orderly manner. Based on Government Regulation No. 18 of 2021 on Right to Manage, Land Rights, Multi-story Housing Units, and Land Registration in Article 87 Paragraph 1,